1998
DOI: 10.1007/s000180050229
|View full text |Cite
|
Sign up to set email alerts
|

A family of major royal jelly proteins of the honeybee Apis mellifera L.

Abstract: The characterization of major proteins of honeybee larval jelly (49-87 kDa) was performed by the sequencing of new complementary DNAs (cDNAs) obtained from a honeybee head cDNA library, by the determination of N-terminal sequences of the proteins, and by analyses of the newly obtained and known sequence data concerning the proteins. It was found that royal jelly (RJ) and worker jelly (WJ) contain identical major proteins and that all the proteins belong to one protein family designated MRJP (from Major Royal J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
341
1
12

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(374 citation statements)
references
References 48 publications
20
341
1
12
Order By: Relevance
“…Other authors also found differences (HAYDAK, 1970;PALMA, 1992;SCHMIDT;BUCHMANN, 1992;LERCKER et al, 1993;SCHMITZOVA et al, 1998;PARFITT, 1999;GARCIA-AMOEDO;ALMEIDA-MURADIAN, 2007) and attributed these differences to the nutritional status of the evaluated colonies, age of mother queens, and the laboratory methods used to analyze their components. Queiroz, Barbosa and Azevedo (2001) reported that supplementation is good, mainly in the Northeast region of Brazil, for royal jelly production throughout the year, including autumn and winter, periods between flowering, in regions of monoculture such as sugarcane plantation, limited pollen flow or low nutritional pollen quality.…”
Section: Physicochemical Quality Of Royal Jelly Samplesmentioning
confidence: 97%
“…Other authors also found differences (HAYDAK, 1970;PALMA, 1992;SCHMIDT;BUCHMANN, 1992;LERCKER et al, 1993;SCHMITZOVA et al, 1998;PARFITT, 1999;GARCIA-AMOEDO;ALMEIDA-MURADIAN, 2007) and attributed these differences to the nutritional status of the evaluated colonies, age of mother queens, and the laboratory methods used to analyze their components. Queiroz, Barbosa and Azevedo (2001) reported that supplementation is good, mainly in the Northeast region of Brazil, for royal jelly production throughout the year, including autumn and winter, periods between flowering, in regions of monoculture such as sugarcane plantation, limited pollen flow or low nutritional pollen quality.…”
Section: Physicochemical Quality Of Royal Jelly Samplesmentioning
confidence: 97%
“…some similarity with the major royal jelly protein from the honeybees [20][21][22], and several yellow-like proteins from other insects [23,24]. Recent studies suggest that the temporal and spatial profiles of Drosophila yellow-y and ebony gene together determine the pattern and intensity of melanization [25], but the mechanism by which the yellow-y gene promotes the formation of pigments is poorly understood.…”
Section: Figure 1 Sequence Alignment Of Drosophila Yellow-f Yellow-fmentioning
confidence: 99%
“…In this family five species of proteins (apalbumin 1-5) with molecular masses ranging from 49-87 kDa have been identified [33]. Apalbumin 3 exists in five isoforms.…”
Section: Introductionmentioning
confidence: 99%
“…Its mRNA has been found expressed in the mushroom bodies of the adult honeybee brain [37] and in the hypopharingeal glands of both nurse bees and foragers [18,36,38]. Apalbumin 1 has been investigated by using cDNA cloning, immunoblotting, SDS-PAGE and 2-DE electrophoresis [15,18,33,35].…”
Section: Introductionmentioning
confidence: 99%